Проблематика відтворення індивідуального стилю автора при перекладі науково-популярної прози - Косенко, А.В.; Беженар, I. В.; Гоца, Н.М. (My University, 2026)
The presented article offers a comprehensive analysis of the peculiarities involved in rendering an author’s individual style in the translation of popular‑science prose. The relevance of the study stems from the growing attention of linguistics and translation studies to idiolect as a key factor determining the communicative effectiveness of a text, as well as from the need to ensure translation adequacy in the context of the increasing dissemination of scientific knowledge. The paper summarizes approaches of Ukrainian and international scholars to defining idiolect, its relationship with the author’s linguistic personality, conceptual worldview, and the pragmatic structure of the text. It is emphasized that popular‑science discourse combines the precision of scientific information with expressiveness, metaphorical aspect, and subjective‑evaluative elements, all of which complicate the translation process. The focus is placed on pragmatic equivalence in translation, which involves preserving the author’s intention, communicative effect, and interpretive strategy. The article analyses the main groups of translation transformations required to adapt the text for a different linguistic audience while maintaining individual stylistic markers. The study highlights the importance of compensating for figurative devices, accurately reproducing authorial metaphors, textual rhythm, and explanatory manner. It is concluded that the successful rendering of idiolect is possible only when scientific accuracy, clarity of exposition, and the stylistic distinctiveness of the original are harmoniously combined. It is additionally emphasized that accounting for the author’s cognitive models and the characteristics of the target audience is essential for shaping a translation strategy that ensures the full reproduction of the text’s pragmatic potential. The prospects for further research include developing a typology of translation challenges and formulating methodological recommendations for translating popular‑science literature.
Keywords: individual style, idiolect, idiostyle, popular‑science prose, communicative intention, pragmatics, translation transformations.